2003
DOI: 10.1046/j.1365-2044.2003.02965.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse airway events during brief nasal inhalations of volatile anaesthetics: the effect of humidity and repeated exposure on incidence in volunteers preselected by response to desflurane*

Abstract: SummaryTwelve volunteers known to have airways that responded adversely to 2.0 MAC desflurane were recruited. Each volunteer inhaled three single breaths of each of 0.5, 1.0 and 2.0 MAC of sevoflurane, halothane, isoflurane, desflurane and balance air, with breaths of air between, whilst breathing nasally through a face mask attached to one of three filters that provided three different levels of humidification. The incidence of any adverse airway events was recorded. The anaesthetic inhaled significantly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Wilkes et al stated that desflurane was the most irritant agent of the upper respiratory tract. [6] Cervin and Lindberg found that NK1 receptors are influenced in airway irritants and atropine does not decrease the early ciliary beat frequency due to desflurane. Use of NK1 antagonists may prevent the elongation of SNTT.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Wilkes et al stated that desflurane was the most irritant agent of the upper respiratory tract. [6] Cervin and Lindberg found that NK1 receptors are influenced in airway irritants and atropine does not decrease the early ciliary beat frequency due to desflurane. Use of NK1 antagonists may prevent the elongation of SNTT.…”
Section: Discussionmentioning
confidence: 98%
“…The high standards of the anesthesia machines, the presence of monitors continuously monitoring and analyzing the gas composition and the increased knowledge of pharmacodynamics and pharmacokinetics of inhaled anesthetics has greatly simplified the safe use of low-flow anesthesia. [6] The humidity and heat of anesthetic gases increases greatly in low-flow anesthesia techniques. Low-flow anesthesia, not only improves the environment, but also significantly reduces the consumption of anesthetic gases and volatile agents, thereby providing cost savings and a reduction in operating room and atmospheric pollution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of anesthetic gases on mucociliary clearance have also been investigated in studies performed before and after the patients received anesthesia (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Wilkes et al demonstrated that humidification of inspired gases did not reduce the incidence of adverse airway events [13]. There was a suggestion from that study that exposure to small concentrations of isoflurane or desflurane may decrease the incidence of adverse airway incidents.…”
mentioning
confidence: 99%